2011
DOI: 10.1016/j.trf.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of self-reported dangerous driving behaviours among a young cohort

Abstract: Background: Young motorists engaging in antisocial and often dangerous driving manoeuvres (which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Here, the determination of the socio-demographic characteristics of those groups at greatest risk of drug driving is crucial. In line with previous studies [ 40 , 41 ], our results show that male drivers are more likely to test positive for drugs than females. However, an examination of recent trends in drunk-driving indicates that the gender gap is narrowing in terms of the number of DUI arrests [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Here, the determination of the socio-demographic characteristics of those groups at greatest risk of drug driving is crucial. In line with previous studies [ 40 , 41 ], our results show that male drivers are more likely to test positive for drugs than females. However, an examination of recent trends in drunk-driving indicates that the gender gap is narrowing in terms of the number of DUI arrests [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Between 28 percent (Cammisa et al 1999) and 70 percent (Garcia-Espana et al 2009) of novices reported having either their own vehicle or primary access to a vehicle at licensure, with ownership rates increasing during the intermediate period (Williams et al 2006). Different methodologies including surveys, interviews, instrumented vehicles, and travel diaries in cross-sectional and longitudinal research have revealed that car ownership is associated with more risky driving behavior, such as speeding (e.g., Cammisa et al 1999;Garcia-Espana et al 2009), particularly at night and while carrying their friends as their passengers (e.g., Klauer et al 2011), crashes (e.g., Williams et al 2006) including "hooning" (i.e., illegal street racing) crash involvement (e.g., Palk et al 2011), offenses (e.g., Hirsch et al 2006, and greater mileage (e.g., Leaf et al 2008). Moreover, greater duration of ownership corresponds to more offenses by and crashes involving young novice drivers (Williams et al 2006).…”
mentioning
confidence: 99%
“…Assessing risky driving poses methodological concerns. Researchers have typically been forced to rely on subjective data, such as self-reported risk behaviors (e.g., Mitchell, Bambach, & Friswell, 2014; Palk, Freeman, Kee, Steinhardt, & Davey, 2011) and police reports (e.g., Schneider, Savolainen, Van Boxel, & Beverley, 2012; Zhou, Roshandeh, Zhang, & Ma, 2016). The validity of self-reported behavior has been called into serious question (see af Wåhlberg, 2009), and police reports rely on inferences as to the cause of a collision.…”
mentioning
confidence: 99%